"Por ahora"/ "de momento"/ "por el momento, es un tipo encantador". Operadores de debilitamiento argumentativo de origen temporal - Montolío Durán, Estrella (Círculo de Lingüística Aplicada a la Comunicación, 2013)
Gramatical and semantic-pragmatic features of adverbial expressions por ahora, de momento, and por el momento are described, showing that they have some of the properties that define discourse markers but also other properties outside the category; they are therefore not fully grammaticalized as markers. From a temporal-aspectual value, these markers evolve towards an epistemic meaning of ‘provisionality of the truth of the utterance’, thus weakening the speaker’s commitment to the future truth value of the utterance, and frequently developing a predictive value announcing a counterargument in the following discourse, so that these markers function as argumentweakening operators.
Keywords: Discourse markers; argument- weakening operators; por ahora; de momento; por el momento.